Structures and strategies for retaining an international pediatric cohort from birth: Lessons from The Environmental Determinants of Diabetes in the Young (TEDDY) study - Patricia Gesualdo; Jessica Melin; Rachel Karban; Claire Crouch; Michael Killian; Diane Hopkins; Annika Adamsson; Joanna Stock; Suzanne Bennett Johnson; Judith Baxter (Contemporary Clinical Trials Communications, 2025)
Background: Retention of study participants in observational studies is essential to maintaining the representativeness of the population, minimizing selection bias, and assuring sufficient statistical power. The aim of this report is to describe the structures and strategies used to retain participants in The Environmental Determinants of Diabetes in the Young (TEDDY) Study, an observational study of children at increased genetic risk for type 1 diabetes followed in an intensive protocol from birth until age 15. Methods: Teague et al.’s systematic review of study retention strategies identified four domains: barrier reduction; community building; follow-up/reminder; and tracing strategies (1). TEDDY retention strategies were categorized into each of these domains. A fifth category presented strategies unique to TEDDY. Results: TEDDY employed over one hundred retention strategies during the 15 years of follow-up; many could be categorized within the Teague domains. Strategies unique to TEDDY included (1) study structures to support retention; (2) risk communication and education strategies specific to this population; (3) Data-informed retention strategies that addressed protocol challenges in real-time; and (4) implementation of a re-engagement protocol for those who had withdrawn from the study. Conclusion: Pediatric cohort studies should include strategies, structures, and resources to address retention at the study's initiation and on an ongoing basis. Retention strategies should not remain static but change with the developmental needs of the child. Collecting and analyzing data on an ongoing basis permits retention strategies to be put in place to address protocol and retention challenges in real time. Trial registration: ClinicalTrials.gov Identifier: NCT00279318.